2017
DOI: 10.1590/1089-6891v18e-41359
|View full text |Cite
|
Sign up to set email alerts
|

Acúmulo De Forragem Durante O Período De Ocupação Dos Animais Em Pastos Sob Lotação Intermitente

Abstract: ResumoO objetivo deste trabalho foi avaliar o acúmulo de forragem durante o período de ocupação pelos animais em pastos de capim-quicuiu (Pennisetum clandestinum Hochst. Ex. Chiov.) manejados sob lotação intermitente. Os tratamentos consistiram de quatro proporções de desfolhação (remoção de 40, 50, 60 e 70% da altura inicial) partindo de uma mesma altura em pré-pastejo (20 cm). Foram avaliadas: taxas de alongamento foliar e colmos e senescência de folhas, índice de área foliar e taxa de acúmulo de forragem. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
0
0
Order By: Relevance
“…Diavão et al [85] conducted a study on the effect of different defoliation strategies (40%, 50%, 60%, and 70% of initial height) in Pennisetum clandestinum pastures managed under intermittent stocking. They found that it was possible to estimate forage accumulation using the marked tiller technique [86].…”
Section: Models To Determine the Forage Accumulation Rate In Tropical...mentioning
confidence: 99%
“…Diavão et al [85] conducted a study on the effect of different defoliation strategies (40%, 50%, 60%, and 70% of initial height) in Pennisetum clandestinum pastures managed under intermittent stocking. They found that it was possible to estimate forage accumulation using the marked tiller technique [86].…”
Section: Models To Determine the Forage Accumulation Rate In Tropical...mentioning
confidence: 99%